2020
DOI: 10.1177/1471301220932780
|View full text |Cite
|
Sign up to set email alerts
|

Robot companion cats for people at home with dementia: A qualitative case study on companotics

Abstract: The use of robot companion pets for people in care homes has been extensively studied. The results are largely positive and suggest that they are valuable in enhancing wellbeing, communication and behavioural aspects. However, there has been little research in people’s own homes, possibly due to the cost and complexity of some of the robot pets currently available. As dementia affects people in different ways, this study explores the effects of a robot cat for people in their own homes, without specifically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Most had appropriate research designs (n=4) [ 40 - 43 ] and recruitment strategies (n=5) [ 40 , 41 , 43 - 45 ]. However, the data collection and analysis methods were not clearly described in 4 studies [ 42 , 46 , 47 ]. These factors subject the studies to assessor bias and reporting biases [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most had appropriate research designs (n=4) [ 40 - 43 ] and recruitment strategies (n=5) [ 40 , 41 , 43 - 45 ]. However, the data collection and analysis methods were not clearly described in 4 studies [ 42 , 46 , 47 ]. These factors subject the studies to assessor bias and reporting biases [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority (n=5) used the JfA robotic cat [ 40 , 42 , 43 , 45 , 47 ], while the others (n=4) employed both the robotic cat and dog [ 41 , 44 , 46 , 50 ]. Only 1 study offered participants’ their choice of robotic pet (ie, cat or dog) and reported no differences between the type of pet to the intervention outcomes [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…University RECs are not recognised by the Secretary of State and therefore cannot legally review proposals that invoke the MCA (HRA, 2019). I am aware of instances in which university RECs have reviewed and approved research that falls under the MCA (for recent examples, see Griffiths et al, 2019Griffiths et al, , 2020Orfanos et al, 2020;Pike et al, 2020;Shoesmith et al, 2020). This appears to arise due to an interpretation of the MCA as only applying to research involving participants who lack capacity, and therefore not applying to research involving people with a diagnosis who do not lack capacity.…”
Section: Governing Capacitymentioning
confidence: 99%